2017
DOI: 10.1039/c7qo00012j
|View full text |Cite
|
Sign up to set email alerts
|

Aroyl chlorides as novel acyl radical precursors via visible-light photoredox catalysis

Abstract: Abundant and inexpensive aroyl chlorides have been employed for the first time as novel acyl radical precursors in visible-light photocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 63 publications
1
45
0
Order By: Relevance
“…Photoexcitation of the photocatalyst Ir(ppy) 3 produces the long‐lived excited *Ir(ppy) 3 ( t 1/2 =1.9 μs, E 1/2 IV/III* =−1.73 V vs. SCE) . In the presence of 2,6‐di‐ tert ‐butyl‐4‐methyl‐pyridinium species, the aroyl chloride IIa ( E p of benzoyl chloride=−1.02 V vs. SCE) undergoes a PCET process with *Ir(ppy) 3 to liberate 2,6‐di‐ tert ‐butyl‐4‐methyl‐pyridine and the α‐chloro‐α‐hydroxy benzyl radical IIb . This nucleophilic radical adds to an alkene to give the intermediate IIc followed by 1,3‐chlorine atom shift to afford the α‐hydroxy radical IId .…”
Section: Methodsmentioning
confidence: 99%
“…Photoexcitation of the photocatalyst Ir(ppy) 3 produces the long‐lived excited *Ir(ppy) 3 ( t 1/2 =1.9 μs, E 1/2 IV/III* =−1.73 V vs. SCE) . In the presence of 2,6‐di‐ tert ‐butyl‐4‐methyl‐pyridinium species, the aroyl chloride IIa ( E p of benzoyl chloride=−1.02 V vs. SCE) undergoes a PCET process with *Ir(ppy) 3 to liberate 2,6‐di‐ tert ‐butyl‐4‐methyl‐pyridine and the α‐chloro‐α‐hydroxy benzyl radical IIb . This nucleophilic radical adds to an alkene to give the intermediate IIc followed by 1,3‐chlorine atom shift to afford the α‐hydroxy radical IId .…”
Section: Methodsmentioning
confidence: 99%
“…For example, acyl radicals could be achieved either by SET oxidation of a-keto acids, 18a-d acyl silanes, 18e or 4-acyl dihydropyridine derivatives, 18f,g or upon SET reduction of hypervalent iodine reagent. 19a,b Acyl chlorides 21 and anhydrides 22 are rarely used in acyl radical chemistry, 23 since the radical formation can be further complicated by polar side reactions. 24 In addition, these substrates are not easily prone to SET activation.…”
Section: Acyl Radical Formation and Applicationsmentioning
confidence: 99%
“…83 Only recently, photoredox catalysis was used for acyl radical formation from acyl chloride. 84 In 2017, Xu et al reported the first protocol to convert a benzoyl chloride to a benzoyl radical, which then reacts with 1,7-enynes to form fused pyran derivatives (Scheme 82). 84a The reaction starts with excitation of fac -Ir(ppy) 3 by blue LED and then the excited fac -*Ir(ppy) 3 ( E ½ IV/III* = ‒1.73 V vs. SCE) 56 is involved in single electron reduction of a benzoyl chloride ( E p = –1.02 V vs. SCE) 84b forming fac -Ir IV (ppy) 3 and benzoyl radical ( 82.2 ).…”
Section: Acyl Chlorides As a Source Of Acyl Radicalsmentioning
confidence: 99%
“…84 In 2017, Xu et al reported the first protocol to convert a benzoyl chloride to a benzoyl radical, which then reacts with 1,7-enynes to form fused pyran derivatives (Scheme 82). 84a The reaction starts with excitation of fac -Ir(ppy) 3 by blue LED and then the excited fac -*Ir(ppy) 3 ( E ½ IV/III* = ‒1.73 V vs. SCE) 56 is involved in single electron reduction of a benzoyl chloride ( E p = –1.02 V vs. SCE) 84b forming fac -Ir IV (ppy) 3 and benzoyl radical ( 82.2 ). The benzoyl radical then attacks the carbon-carbon double bond of 82.3 to afford an alkyl radical intermediate 82.4 , which undergoes radical cyclization with the alkyne triple bond to form a vinyl radical intermediate 82.5 .…”
Section: Acyl Chlorides As a Source Of Acyl Radicalsmentioning
confidence: 99%